Phase I/Ib Study of Olaparib and Carboplatin in BRCA1 or BRCA2 Mutation-Associated Breast or Ovarian Cancer With Biomarker Analyses. (19th May 2014) - Lee, Jung-Min; Hays, John L.; Annunziata, Christina M.; Noonan, Anne M.; Minasian, Lori; Zujewski, Jo Anne; Yu, Minshu; Gordon, Nicolas; Ji, Jiuping; Sissung, Tristan M.; Figg, William D.; Azad, Nilofer; et al.
Abstract: Background: Olaparib has single-agent activity against breast/ovarian cancer (BrCa/OvCa) in germline BRCA1 or BRCA2 mutation carriers ( gBRCAm ). We hypothesized addition of olaparib to carboplatin can be administered safely and yield preliminary clinical activity. Methods: Eligible patients had measurable or evaluable disease, gBRCAm, and good end-organ function. A 3 + 3 dose escalation tested daily oral capsule olaparib (100 or 200mg every 12 hours; dose level1 or 2) with carboplatin area under the curve (AUC) on day 8 (AUC3 day 8), then every 21 days. For dose levels 3 to 6, patients were given olaparib days 1 to 7 at 200 and 400 mg every 12 hours, with carboplatin AUC3 to 5 on day 1 or 2 every 21 days; a maximum of eight combination cycles were permitted, after which daily maintenance of olaparib 400mg every12 hours continued until progression. Dose-limiting toxicity was defined in the first two cycles. Peripheral blood mononuclear cells were collected for polymorphism analysis and polyADP-ribose incorporation. Paired tumor biopsies (before/after cycle 1) were obtained for biomarker proteomics and apoptosis endpoints. Results: Forty-five women (37 OvCa/8 BrCa) were treated. Dose-limiting toxicity was not reached on the intermittent schedule. Expansion proceeded with olaparib 400mg every 12 hours on days 1 to 7/carboplatin AUC5. Grade 3/4 adverse events included neutropenia (42.2%), thrombocytopenia (20.0%), and anemia (15.6%). Responses included 1 complete response (1 BrCa; 23 months) and 21 partial responses (50.0%; 15 OvCa; 6 BrCa; median = 16 [4 to >45] in OvCa and 10 [6 to >40] months in BrCa). Proteomic analysis suggests high pretreatment pS209-eIF4E and FOXO3a correlated with duration of response (two-sided P < .001; Pearson's R 2 = 0.94). Conclusions: Olaparib capsules 400mg every 12 hours on days 1 to 7/carboplatin AUC5 is safe and has activity in gBRCAm BrCa/OvCa patients. Exploratory translational studies indicate pretreatment tissue FOXO3a expression may be predictive for response to therapy, requiring prospective validation.